UMP Vice Chancellor won National Book Award 2013 - Muhammad Azli, Shukri (Penerbit UMP, 2013)
Kuala Lumpur, December 11- A book written by Universiti Malaysia Pahang's Vice Chancellor Professor Dato' Dr Daing Nasir Ibrahim titled 'Universiti: Watak, Budaya dan Citra' (University: Character, Culture and Image) was announced as the recipient of National Book Award 2013 for the Best Administrative General Book Category.